Reconceptualizing Reactivity of Think‐Alouds and Eye Tracking: Absence of Evidence Is Not Evidence of Absence. Issue 4 (8th October 2015) - Godfroid, Aline; Spino, Le Anne
<x xml:space="preserve">Abstract</x> This study extends previous reactivity research on the cognitive effects of think‐alouds to include eye‐tracking methodology. Unlike previous studies, we supplemented traditional superiority tests with equivalence tests, because only the latter are conceptually appropriate for demonstrating nonreactivity. Advanced learners of English read short English texts embedded with pseudowords in an eye‐tracking (n = 28), think‐aloud (n = 28), or silent control condition (n = 46). Results indicated that neither eye tracking nor thinking aloud affected text comprehension. In terms of vocabulary recognition, thinking aloud had a small, positive effect, and the results for eye tracking were mixed. We discuss challenges and opportunities of equivalence testing and explore ways to improve study quality more generally in second language acquisition research.